TEACHING ENGLISH TO DISABLED LEARNERS (Spectrum Journal of Innovation, Reforms and Development, 2022)
In this article one of the most vital topics has been discussed. As teaching and learning English is required from all of us, so the young and old should know English. However, some of them may not be able to learn because of some illness such as dyslexia, dysgraphia, attention deficit disorder attention and deficit hyperactivity. Some useful tips and advice have been given in the article.